2018
DOI: 10.3389/fcvm.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Cardiomyopathies and the Role of Mutations in Non-coding Regions of the Genome

Abstract: Cardiomyopathies (CMs) are a group of cardiac pathologies caused by an intrinsic defect within the myocardium. The relative contribution of genetic mutations in the pathogenesis of certain CMs, such as hypertrophic cardiomyopathy (HCM), arrythmogenic right/left ventricular cardiomyopathy (ARVC) and left ventricular non-compacted cardiomyopathy (LVNC) has been established in comparison to dilated cardiomyopathy (DCM) and restrictive cardiomyopathy (RCM). The aim of this article is to review mutations in the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…In recent years, several studies (41,42) have investigated the functions and clinical implications of non-coding RNAs in HCM. However, the impact of RNA crosstalk on HCM has not been previously addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies (41,42) have investigated the functions and clinical implications of non-coding RNAs in HCM. However, the impact of RNA crosstalk on HCM has not been previously addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs, lncRNAs and TFs that interact with the co-expressed key genes were then screened to obtain a multi-factor regulatory network. To date, several studies have reported the features of ncRNAs in the HOCM (Ntelios et al, 2017;Salman et al, 2018). Nevertheless, the details of RNA crosstalk in HOCM have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…According to Salman et al, 2018, there is a substantial amount of pathogenic intronic mutations, namely about 10%, which may alter splicing mechanisms [ 125 ]. Thereby, insertions or deletions occur which may alter the reading frame and induce a premature stop codon leading to a truncated protein.…”
Section: Molecular Mechanisms In Rcmmentioning
confidence: 99%
“…The resulting contractile dysfunction might impair the structural integrity of sarcomeres and, in concert with altered protein expression and altered interactions with associated proteins as well as altered post-translational modifications, might pivotally contribute to the specific phenotype. In addition, it is thought that modifiers as sex hormones, polymorphisms in other genes (exons and introns) or even other mutations also contribute to the disease phenotype [ 125 , 144 , 145 ]. A specific feature of RCM is protein aggregation.…”
Section: Problems and Prospects In Rcmmentioning
confidence: 99%